2020
DOI: 10.3390/math8091589
|View full text |Cite
|
Sign up to set email alerts
|

Research Analysis on Emerging Technologies in Corporate Accounting

Abstract: The technological transformation has directly affected the functional areas of companies. This circumstance has been a challenge for corporate accounting, since the emerging technology allows handling a large volume of data, and providing valuable information for operational management, managerial control, and strategic planning. The aim of this study is to analyze current and future lines of research globally, during the period 1961–2019, on emerging technologies in corporate accounting. For this, bibliometri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 21 publications
(12 citation statements)
references
References 130 publications
0
9
0
Order By: Relevance
“…The keywords were defined to associate accountants or the accounting profession with emerging technologies. To broaden the emerging technologies research scope, we included terms identified by Abad-Segura and González-Zamar [29], as well as two terms to check for other types of emerging technologies. Regarding accounting, we searched for words representing accounting as a profession, or professional or scientific area.…”
Section: Article Collectionmentioning
confidence: 99%
See 1 more Smart Citation
“…The keywords were defined to associate accountants or the accounting profession with emerging technologies. To broaden the emerging technologies research scope, we included terms identified by Abad-Segura and González-Zamar [29], as well as two terms to check for other types of emerging technologies. Regarding accounting, we searched for words representing accounting as a profession, or professional or scientific area.…”
Section: Article Collectionmentioning
confidence: 99%
“…When approaching emerging technologies, we focus on research that connects the concept of emerging technology with impacts on the accounting profession, which helps us limit our search. Nevertheless, we found a study by Abad-Segura and González-Zamar [29], who analyzed the research on emerging technologies in corporate accounting from 1961-2019. They identified the main terms recently associated with new technology and digitalization related to accounting as big data, blockchain, social media, and artificial intelligence.…”
Section: Introductionmentioning
confidence: 99%
“…The explicit objective of this methodology is to search, identify, organize, and analyze the trends of the research topic, in addition to the intellectual representation of a scientific discipline [51,52]. Studies on the scientific literature make it possible to identify certain relationships between the documents of a certain research area and, in this way, to observe the influence of authors, recognize subdisciplines, or trace the historical development and progress in an area of interest [53,54].…”
Section: Methodsmentioning
confidence: 99%
“…The explicit objective of this methodology is to search, identify, organize and analyze the trends of the research topic [62,63]. In recent decades, bibliometrics has contributed to the review of scientific knowledge and has been used successfully in different scientific fields [64][65][66]. The aim is to show a vision of the development of research related to management accounting for healthy nutrition education.…”
Section: Methods and Data Selectionmentioning
confidence: 99%